PERSEPSI DOSEN TERHADAP INTEGRASI NILAI-NILAI KARAKTER PADA MATAKULIAH KEAHLIAN BERKARYA (MKB) DI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU - Evi Suryawati; Yustini Yusuf; Ruth Cahaya (Biogenesis, 2013)
This researh aims to determine the perceptions of lecturers towards integration MKB Character Education in Biology Faculty of Teacher Education Program University of Riau. The research was conducted in May-August 2012. The parameters of this research are the perception and understanding lecturers. The data technique collecting is closed questionaires and open questionnaires to determine lecturer perceptions of the character education and tests to determine lecturer understanding. Enclosed questionaire consisted of two indicators: (1) character education with 4 sub-indicators and (2) implementation of character education with 2 sub-indicators. Comprehension test has two indicators: (1) character education with 5 sub-indicators and (2) development of character education with 3 sub-indicators. The data technique analyze are descriptive analyze.Keywords: Character Value, MKB, Perception.